1962
DOI: 10.1038/bjc.1962.35
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glucose and Lactate Content of Ascites Fluid and Blood Plasma During Growth and Decay of the ELD Ascites Tumour

Abstract: WHEN considering the nutritional and transport facilities of tumours one is struck by the diverging conditions developing in ascites and solid tumours with time. Early transplants of both solid and ascites tumours seem close enough to the vascular svstem of the host. In the case of solid tumours, with increasing age and size, vascular occlusion and deranged interstitial transport facilities (Goldacre andSylven, 1959, 1962) lead to starvation and cell death in central tumour regions. In ascites tumours the regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1965
1965
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 7 publications
(5 reference statements)
1
10
0
Order By: Relevance
“…Excess lactate in muscle is excreted, leading to a rapid increase in blood lactate levels and the acidification of the microenvironment. Previous studies have shown that a significant amount of cancer lactate is released into the blood 39,40 . Furthermore, endurance training has also been shown to reduce circulating lactate concentrations, consistent with our findings 19 .…”
Section: Discussionsupporting
confidence: 92%
“…Excess lactate in muscle is excreted, leading to a rapid increase in blood lactate levels and the acidification of the microenvironment. Previous studies have shown that a significant amount of cancer lactate is released into the blood 39,40 . Furthermore, endurance training has also been shown to reduce circulating lactate concentrations, consistent with our findings 19 .…”
Section: Discussionsupporting
confidence: 92%
“…In tumorbearing mice, the results are unclear, with some investigators reporting no change in fasting plasma lactic acid levels,*L and others reporting increased levels. 43 In one study with a rat sarcoma model, the authors demonstrated elevated plasma levels, but this was done with very large tumors, and the nutritional status was not ~t a t e d . "~ In this model, tumor-bearing animals demonstrated a significant elevation of blood lactic acid concentration when compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…it is much higher than the concentration of 3 mg/100 ml. required to sustain glycolysis of Ehrlich ascites cells (Kemp and Mendel, 1957;Burgess and Sylven, 1962). Thus glucose deficiency and injurious concentrations of carbon dioxide or lactic acid appear not to be primary causes of cell death in tumours.…”
Section: Causes Of Cell Deathmentioning
confidence: 99%